The time has come for revising the rules of clozapine blood monitoring in Europe. A joint expert statement from the European Clozapine Task Force - Hélène Verdoux; Robert A. Bittner; Alkomiet Hasan; Mishal Qubad; Elias Wagner; Alexis Lepetit; Manuel Arrojo-Romero; Christian Bachmann; Marieke Beex-Oosterhuis; Jan Bogers; Andreja Celofiga; Dan Cohen; et al. (European Psychiatry)
The European Clozapine Task Force is a group of psychiatrists and pharmacologists practicing in 18 countries under European Medicines Agency (EMA) regulation, who are deeply concerned about the underuse of clozapine in European countries. Although clozapine is the most effective antipsychotic for people with treatment-resistant schizophrenia, a large proportion of them do not have access to this treatment. Concerns about clozapine-induced agranulocytosis and stringent blood monitoring rules are major barriers to clozapine prescribing and use. There is a growing body of evidence that the incidence of clozapine-induced agranulocytosis is very low after the first year of treatment. Maintaining lifelong monthly blood monitoring after this period contributes to unjustified discontinuation of clozapine. We leverage recent and replicated evidence on the long-term safety of clozapine to call for the revision and updating of the EMA’s blood monitoring rules, thus aiming to overcome this major barrier to clozapine prescribing and use. We believe the time has come for relaxing the rules without increasing the risks for people using clozapine in Europe.